Life expectancy and health care utilization of individuals with dementia in Ontario, Canada: A population-level study - Fisher, Stacey; Manuel, Douglas G; Spruin, Sarah; Anderson, Geoffrey; Taljaard, Monica; Tanuseputro, Peter (International Journal of Population Data Science, 2020)
Introduction It is important for dementia patients, their families and caregivers, and health planners to have an understanding of life expectancy and the likely care experience of patients from dementia diagnosis to end-of-life. Objectives and Approach Using administrative health data of all dementia patients in Ontario, Canada (2014 to 2017) and period life table methodology, life expectancy and average health care use and cost for individuals from dementia diagnosis to death was examined. Dementia was ascertained by a validated case ascertainment definition and information from long-term care, home care and complex continuing care assessments. Formal care was categorized as inpatient, outpatient, home care or long-term care. Results Life expectancy at dementia diagnosis was 8.7 years and 9.8 years for men and women diagnosed prior to age 75, of which 3.7 years (42%) and 4.7 years (49%) was spent receiving formal care, respectively. Life expectancy was 4.4 and 5.2 years for men and women diagnosed after age 75, of which 2.2 years (50%) and 3.1 years (60%) was spent receiving care, respectively. Women received proportionally more long-term and home care compared to men, while men received more inpatient and outpatient care. In the year prior to dementia diagnosis, individuals received formal care for 20 days per 100 person-days. Those at the end-of-life received care for 79 days per 100 person-days, including 55 long-term care days and 7.8 inpatient care days. Average direct health care costs from diagnosis to end-of-life was 230,000 and was higer for women and those diagnosed before age 75. Conclusion The burden of formal care for those with dementia is substantial. The results of this study will be used by physicians to inform conversations with patients, their families and caregivers around what to expect after a dementia diagnosis, and by health care planners for population health planning.